The Acting Class and the Myths of Meritocracy. Issue 1 (January 2022) - O'Neill, Deirdre; Wayne, Mike
Abstract : Our feature documentary The Acting Class (2017) is here contextualised in the context of a critique of the cultural industries as part of the ideology of meritocracy and a resurgence of work around class in the sociology of culture. The Acting Class focuses on the question of class stratification in the UK acting industry. We here review our research on this issue and contextualise it within the scholarly literature on diversity and inequality, the creative industries and the broader reconfigurations of the political economy of British capitalism. We also discuss the importance of the interview in creative practice research as a way of democratising knowledge production and socialising experience.